The Identification of Quality Of Life in Glaucoma Patients at Balung Regional Hospitals - Sinura, Zhindy; Siswoyo; Nistiandani, Ana (Al-Hijrah Indonesia, 2024)
Glaucoma is a chronic neurodegenerative disorder of the optic nerve characterized by an increased IOP and progressive. The main threat to patients with visual impairment is the gradual loss of vision. Decreased vision function in glaucoma patients and inability to adapt to changes in body functions will have an impact on the ability to carry out daily activities and will affect the quality of life. The aim of this study was to analyze the quality of life in glaucoma patients at the Jember Regency Balung Regional Hospital. This study used a quantitative descriptive with a cross- sectional approach. 97 respondent were treated at Poli Mata Hospital in Balung Regional Hospital, Jember Regency obtained by purposive sampling technique. Collected data using the National Eye Institute Visual Function Questionnaire-25 (NEI-VFQ 25). Data analysis using univariate. The results of the study were 49 respondents (50,5%) had a qood quality of life and 48 respondents (49,5%) had a less quality of life, near vision is the most problematic subscale in all of domains. The quality of life of glaucoma patients is a good category, which means respondents are satisfied with their health and vision condition does not significantly interfere with daily activities. Respondents can still do their daily activities independently even though slightly limited, both with and without glasses.